Colorectal wall regeneration resulting from the association of chitosan hydrogel and stromal vascular fraction from adipose tissue. Issue 2 (23rd October 2017) - Denost, Quentin; Pontallier, Arnaud; Buscail, Etienne; Montembault, Alexandra; Bareille, Reine; Siadous, Robin; Durand, Marlene; Delmond, Samantha; David, Laurent; Bordenave, Laurence
Abstract: Chitosan hydrogel and adipose derived stem cells (ADCS) have been reported as the optimal partnership for colorectal tissue engineering. In that field, the aim of the current experiment was to assess the interest of seeding ADSC on chitosan hydrogel patches in an in vivo comparative study and on a tube intended replace a colonic segment in an in vivo feasibility study. In the comparative study, a 2 × 3 cm colonic wall defect was performed in 20 swine and repaired by suturing a chitosan hydrogel patch: acellular matrix (group A, n  = 10) versus matrix seeded with autologous stromal vascular fraction (SVF) (group B, n  = 10). In the feasibility study, a circular colonic section was performed and a 2‐cm‐length chitosan hydrogel tube (seeded with autologous SVF) was implanted between the two edges of the colon in 3 pigs. Graft areas were explanted at 8 weeks for examinations. Endpoints were technical feasibility, fibrosis ratio, and smooth muscle layer regeneration. A complete coverage of the patched area was observed with an ad integrum regeneration of the colonic wall including smooth muscle cells layer around a thin fibrosis scare. Fibrosis ratio was significantly lower group B: 13% versus 55% ( p  = 0.013). Segmental colonic replacement appeared accurate. Our data confirmed in a large animal model the healing effect of chitosan on colorectal tissue. The very low rate of the fibrosis ratio in the cellularized group emphasizes inflammatory control effect of the chitosan hydrogel and SVF association. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 460–467, 2018.